Multidrug-resistant Pseudomonas aeruginosa in healthcare facilities in Port-au-Prince, Haiti. (June 2021) - McAulay, Kathrine; Schuetz, Audrey N.; Fauntleroy, Kathy; Shen, Lishuang; Merveille, Yves-Mary; Deroncelay, Alexandra; Cole, Nicolynn; Fitzgerald, Daniel W.; Ocheretina, Oksana
Highlights: High-risk, carbapenem-resistant Pseudomonas aeruginosa clones were detected in clinical isolates from Haiti. Multidrug-resistant phenotypes were observed both in new and established sequence types. Colistin resistance was detected in two clinical isolates tested in this study. Abstract: Objectives: Pseudomonas aeruginosa is a leading cause of opportunistic infections worldwide, particularly in healthcare settings, and frequently demonstrates resistance to commonly prescribed antimicrobials. Carbapenem resistance is prevalent worldwide, however there are currently limited data available from Haiti. The aim of this study was to characterise and document this phenotype in Port-au-Prince, Haiti, to further inform the need for appropriate infection control, empirical treatment guidelines and laboratory screening measures, both in Haiti and globally. Methods: A total of 50 P. aeruginosa isolates were characterised by multilocus sequence typing (MLST) and antimicrobial susceptibility testing, of which 8 isolates were also subjected to whole-genome sequencing (WGS) to identify potential genetic correlations of phenotypic resistance. Results: By MLST, 23 sequence types (STs) were identified, including 13 new STs. Nineteen isolates belonged to a single, previously characterised ST (ST654), all of which demonstrated a multidrug-resistant phenotype, including resistance to meropenem, imipenem and ceftazidime; two isolates were also resistant to colistin. WGS revealed the presence of genes encoding several previously characterised resistance determinants in ST654; notably ACC(6′)-Ib3-cr and GES-7. Metallo-β-lactamase genes ( bla VIM-5 ) were also detected in three isolates. Conclusion: These findings confirm that drug-resistant clones of P. aeruginosa are present in Haiti, supporting the need for appropriate screening and control measures and confirming that drug-resistant micro-organisms pose a global threat. Further investigations are required to guide appropriate antimicrobial prescribing in this region.